2015
DOI: 10.1021/acs.orglett.5b02375
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of 2-Chloropyrimidin-4-ol Derivatives: An Unusual Reactivity of Thiophosgene

Abstract: A novel, high-yielding, one-step synthesis of 2-chloroquinazolin-4-ols and analogous bicycles from 2-aminoamides using thiophosgene is described. The scope of the reaction includes aminothioamides, amino acids, and fused heterocycle derivatives, furnishing quinazolines, oxazinones, and substituted fused pyrimidine bicycles, respectively. On the basis of observed results with substituted analogues, a mechanism for this transformation is thought to occur via an isothiocyanate intermediate followed by an unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Isatoic anhydrides are valuable synthetic intermediates in the preparation of biologically important compounds in medicinal chemistry. , They have also been well-validated as a SHAPE (selective 2′-hydroxyl acylation analyzed by primer extension) reagent in RNA structure probing chemistry . In general, isatoic anhydrides are synthesized by cyclization reactions of anthranilic acids using phosgene or its substitutes (Scheme , a ), ,,, or oxidative reactions of indoles or isatins (Scheme , b ) . Despite their practicality, these approaches involve the use of highly toxic phosgene reagents/stoichiometric oxidants and require the multistep synthesis of starting materials.…”
mentioning
confidence: 99%
“…Isatoic anhydrides are valuable synthetic intermediates in the preparation of biologically important compounds in medicinal chemistry. , They have also been well-validated as a SHAPE (selective 2′-hydroxyl acylation analyzed by primer extension) reagent in RNA structure probing chemistry . In general, isatoic anhydrides are synthesized by cyclization reactions of anthranilic acids using phosgene or its substitutes (Scheme , a ), ,,, or oxidative reactions of indoles or isatins (Scheme , b ) . Despite their practicality, these approaches involve the use of highly toxic phosgene reagents/stoichiometric oxidants and require the multistep synthesis of starting materials.…”
mentioning
confidence: 99%
“…An oxidative Pd II ‐catalyzed isocyanide insertion route was developed by Ruijter and co‐workers (Route C) . More recently, a thiophosgene mediated cyclization process was also described for accessing 2‐amino‐benzoxazinones (Route D) . While these synthetic methods are efficient, they suffer from certain disadvantages like the requirement of toxic reagents or gases and poor atom‐economy, which limits their industrial applicability.…”
Section: Methodsmentioning
confidence: 99%
“…No desired product was observed in the absence of Rh II salt demonstrating crucial role played by the Rh-salt for the catalytic generation of electrophilic a-iminocarbenoid species (entry 8). Further screening of Rh-salts showed that Rh 2 (TFA) 4 and [Rh(COD)Cl] 2 were ineffective for promoting the transformation (entries [9][10][11][12].…”
mentioning
confidence: 99%
“…An alternative route to intermediate 11 from compound 18 was also demonstrated (Scheme ). Chlorination of 18 with triphosgene selectively converted 2-SH group to 2-Cl with the 4-OH remaining intact and provided 13b in 81% yield . The chloropyrimidine performs equally well in the S N Ar reaction using prolinol 14 to give compound 11 in 79% yield.…”
mentioning
confidence: 99%
“…Chlorination of 18 with triphosgene selectively converted 2-SH group to 2-Cl with the 4-OH remaining intact and provided 13b in 81% yield. 26 The chloropyrimidine performs equally well in the S N Ar reaction using prolinol 14 to give compound 11 in 79% yield. This approach with better atom economy is complementary to the sulfone route ( Scheme 5 ).…”
mentioning
confidence: 99%